The Beta3 499-513 Peptide Region is Required for AlphaIIb/ Beta3 Active Complex Formation and Fibrinogen Binding - Virginia Woo-Rasberry; Thomas M. Chiang (AboutScience Srl, 2008)
Background: AlphaIIb/beta3 (αIIb/β3) complex is an important integrin that is involved in the ﬁnal step of platelet aggregation. Peptides derived from either αIIb or β3 have demonstrated to have an effect on the activation of the complex and its ability to bind ﬁbrinogen. We have previously deﬁned a peptide from β3, which inhibits agonists-induced platelet aggregation.Methods: We used standard methodologies for construction of clones and expression of cDNAs, establishment of stable cell lines that contained these cDNAs. Expression of proteins was detected with immunoblots. Flow cytometric analyses were used to verify the presence of the active and inactive complexes with different antibodies. In addition, a ﬁbrinogen- binding assay was used to determine the inhibition of the active complex by the peptide.Results and discussion: A stable cell line of the co-transfected cDNAs of αIIb, β3 wild type and mutants of β3 (scrambled sequence of the peptide region, replacement of C499A and C512A), expressing the inactive complex on CHO cells, has allowed us to examine the important role of the peptide sequence and the cysteine residues within the peptide. The peptide inhibits the active complex formation and thereby inhibits the binding of FITC-PAC-1 in a dose dependent manner by ﬂow cytometric analyses, as well as binding of [3H]-ﬁbrinogen. In addition, creation of a second stable cell line containing wild type αIIb and the mutated region of β3 (residues 499-513) shows that the binding of FITC-PAC-1 and [3H]-ﬁbrinogen on the mutant activated complex was much lower than the wild type activated complex. Our results indicate that the region 499-513 in β3 is one of the important sites for αIIb/β3 active complex formation and the cysteines play an important role in the process.